Method Validation of a High Resolution Melting Analysis of a Candidate Genetic Marker of Hypertension - Zumaraga, Mark Pretzel; Rodriguez, Marietta; Timoteo, Vanessa Joy; Tanchoco, Celeste (Journal of the ASEAN Federation of Endocrine Societies, 2015)
Objectives.The study aimed to validate a high resolution melting (HRM) – polymerase chain reaction (PCR) based method for analysis of ATP2B1 rs2681472, a candidate genetic marker for hypertension. Specifically, the study aimed to establish method accuracy, inter- and intra-day precision, instrument detection limits (IDL) and linearity. Methodology. DNA samples from whole blood of selected respondents of the 2008 National Nutrition Survey (NNS) were analyzed for ATP2B1 rs2681472, following the HRM-PCR method. Analytical validation parameters such as method accuracy, inter- and intra-day precision, IDL and assay linearity were evaluated. Results. The data obtained using HRM conformed to data obtained from the current gold standard, which is direct DNA sequence analysis. Precision of the method is shown in the low intra-day and inter-day coefficients of variation of 0.11% and 0.14% respectively. The IDL was found at 1x10-2 ng DNA. Correlation coefficient using the method has met the acceptance criteria for linearity that is equal to 0.98. Conclusion. HRM-PCR was successfully applied for analysis of ATP2B1 rs2681472. HRM is a highly commendable tool that can identify existence of polymorphisms in a genome which may be related to or which may cause hypertension. The method was found to be accurate and precise.